Layered Randomized Quantization for Communication-Efficient and Privacy-Preserving Distributed Learning - Yan, Guangfeng; Li, Tan; Wu, Kui; Song, Linqi (IEEE journal on selected areas in communications, 2025)
In distributed learning systems, ensuring efficient communication and privacy protection are two significant challenges. Although several existing works have attempted to address these challenges simultaneously, they often overlook essential learning-oriented features such as dynamic gradient and communication characteristics. In this paper, we propose a communication-efficient and privacy-preserving distributed SGD algorithm. Our proposed algorithm employs a layered randomized quantizer (LRQ) to reduce communication overhead, which also ensures that quantization errors follow an exact Gaussian distribution, thus achieving client-level differential privacy. We analyze the trade-off between convergence error, communication, and privacy under non-IID data distributions. Besides, we modify the algorithm to be training-adaptive by adjusting the per-round privacy budget allocation in response to i) dynamic gradient features and ii) real-time changing communication rounds. Both closed-form solutions are derived by solving the minimization problem of convergence error subject to the privacy budget constraint. Finally, we evaluate the effectiveness of our approach through extensive experiments on various datasets, including MNIST, CIFAR-10, and CIFAR-100, demonstrating its superiority in terms of communication cost, privacy protection, and model performance compared to state-of-the-art methods.